Innovation Capability as A Mediator in The Relationship Between Learning Orientation and The Performance of Batik SMEs - Rokhman, M. Taufiq Noor; Ratnawati, Ratnawati (Journal of Business Management and Economic Development, 2026)
This study aims to analyze the role of innovation capability as a mediating variable in the effect of learning orientation on MSME performance, developed within a single model and explained by Resource-Based Theory as the main theoretical framework. The population of this study consists of batik MSME actors in the city of Surakarta, Central Java, totaling 459 MSMEs. The sample size was determined using a sample size calculator application through the website raosoft.com, resulting in 210 MSME actors. Furthermore, the sampling technique used was Simple Random Sampling, and the analysis technique employed was Partial Least Squares (PLS). PLS is a structural equation modeling (SEM) approach. The results of the study show that learning orientation has a significant effect on MSME performance and innovation capability. Meanwhile, innovation capability has a significant effect on MSME performance. Innovation capability is also able to mediate the influence of learning orientation on MSME performance. Theoretically, these findings strengthen the knowledge-based view perspective, which emphasizes that learning orientation is a strategic resource capable of improving business performance. Local governments in Central Java need to provide support that is not only in the form of basic training, but also in strengthening the innovation ecosystem through mentoring, access to technology, and facilitating collaboration.